KEUNGGULAN METODE STORY TELLING DALAM MEMBENTUK KUALITAS KARAKTER DAN MORAL MAHASISWA - Sri Dewi Lisnawaty (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2020)
The story telling method is an activity of conveying the story of a story teller to the listener with the aim of providing information for the listener so that it can be used to recognize the emotions of themselves and others, and be able to do problem solving. To develop children's character and morals in this case students certainly cannot use inappropriate methods, one of them is the story telling method, such as telling religious leaders who struggle in spreading Islam, not just telling their struggle, but must tell the character and moral of the character, so that children in this case students can get to know even though they have never met the character, it is for Muslims, if it is Muslim, then the most important thing to tell is how the character and morals of the prophet Muhammad, the goal is that children are able to emulate and also follows all aspects of the principles possessed by the prophet Muhammad, by which story telling is very important to be applied to the development of character and morals of children.